Effect of a Laminarin Rich Macroalgal Extract on the Caecal and Colonic Microbiota in the Post-Weaned Pig - Stafford Vigors (Marine Drugs, 2020)
Dietary supplementation with 300 ppm of a laminarin rich macroalgal extract reduces post-weaning intestinal dysfunction in pigs. A comprehensive analysis of the impact of laminarin on the intestinal microbiome during this period is essential to inform on the mode of action of this bioactivity. The objective of this study was to evaluate the effects of supplementing the diet of newly weaned pigs with 300 ppm of a laminarin rich extract, on animal performance, volatile fatty acids, and the intestinal microbiota using 16S rRNA gene sequencing. Pigs fed the laminarin-supplemented diet had higher average daily feed intake, growth rate, and body weight compared to pigs fed the control diet (p < 0.05). Pigs fed the laminarin-supplemented diet had reduced abundance of OTUs assigned to Enterobacteriaceae and increased abundance of OTUs assigned to the genus Prevotella (p < 0.05) compared to pigs fed the control diet. Enterobacteriaceae had negative relationships (p < 0.05) with average daily feed intake (ADFI), average daily gain (ADG), and butyric acid concentrations. In contrast, Prevotellaceae were positively correlated (p < 0.05) with ADFI, ADG, total VFA, acetic, propionic, butyric acids, and negatively correlated with isovaleric acid. Hence supplementation with a laminarin enriched extract potentially improves performance during the post-weaning period by promoting the proliferation of bacterial taxa such as Prevotella that favourably enhance nutrient digestion while reducing the load of potentially pathogenic bacterial taxa including Enterobacteriaceae.